Low-temperature cracking resistance, fatigue performance and emission reduction of a novel silica gel warm mix asphalt binder. (20th January 2020) - Luo, Haoyuan; Leng, Huikang; Ding, Haibo; Xu, Jiaqiu; Lin, Haoyu; Ai, Changfa; Qiu, Yanjun
Highlights: Silgate is a new three-component warm mix additive using silica gel. Silgate had a similar effect on mixing/compaction temperatures to other additives. Reduced critical cracking temperature and improved low temperature performance. Improved fatigue resistance and reduced emission of carbon-based compounds. Introduced the working mechanism of three kinds of warm mix additives by pictures. Abstract: In this paper, a novel warm mix additive, Siligate, has been developed for applications in low-temperature regions. Its effect on the performance of asphalt binder was compared to Sasobit® and Evotherm®M1 by four tests which include rotational plate viscosity (RPV) test, critical cracking temperature analysis, double-edge-notched tension (DENT) test, and emission test. The results show that the addition of 6 wt% Siligate had a similar ability to 3 wt% Sasobit and 0.8 wt% Evotherm®M1, which can reduce the mixing and compaction temperatures by 13 °C and 14 °C, respectively. After adding above dosage of Siligate, it can significantly reduce the critical cracking temperature of asphalt binders, which are not achievable with the other two additives. It is also the best in fatigue performance enhancements and carbon-based emission reductions.